PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, TOTAL ASSET TURNOVER DAN KEBIJAKAN MANAJERIAL TERHADAP PERTUMBUHAN LABA - Nadia Hanifah; Kartika Hendra; Siti Nurlaela (Oikos : Jurnal Ekonomi dan Pendidikan Ekonomi, 2020)
Earnings growth is an increase in profit or decline in profit per year and can be used to assess how the development of a company's performance. The purpose of this study is to examine and analyze the effect of current ratio, debt to equity ratio, total asset turnover and managerial ownership on earnings growth. The population in this study is the banking sub-sector companies listed on the Indonesia Stock Exchange for the period of 2016-2018. The sampling technique in this study used a purposive sampling method and obtained a sample of 20 companies. The data analysis method uses the classic assumption test and multiple linear regression analysis using SPSS 20, with the results of data analysis showing that, debt to equity ratio and managerial ownership influence earnings growth. While the current ratio and total asset turnover has no effect on profit growth. Keywords : Profit Growth, Current Ratio, Debt to Equity Ratio, Total Aset Turnover, Managerial Ownership